2014
DOI: 10.1542/peds.2013-2166
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Sexual Abuse and Suicidal Behavior: A Meta-analysis

Abstract: BACKGROUND AND OBJECTIVE: Self-inflicted injuries are one of the major causes of disease burden and death globally. Understanding the extent to which this is associated with childhood sexual abuse (CSA) exposure can help inform prevention strategies. We aimed to quantify to what extent CSA was associated with incident suicide attempts in men and women. Longitudinal studies and cotwin analyses from twin studies in any population from any year were eligible for inclusion. Of 22 235 abstracts screened as part of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
84
2
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(104 citation statements)
references
References 51 publications
12
84
2
6
Order By: Relevance
“…Sexually abused adolescent girls are at high risk of suicidal ideation and attempts (Devries et al, 2014;Miller et al, 2013). In our sample, close to half of participants (46%) reported suicidal ideation in the past three months.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Sexually abused adolescent girls are at high risk of suicidal ideation and attempts (Devries et al, 2014;Miller et al, 2013). In our sample, close to half of participants (46%) reported suicidal ideation in the past three months.…”
Section: Discussionmentioning
confidence: 68%
“…Suicide is the first worldwide cause of death among adolescent girls aged 15-19 years (Patton et al, 2009). A recent meta-analysis also indicates that between 20% and 22% of suicide and suicidal attempts among women can be imputed to CSA (Devries et al, 2014).…”
Section: Coping Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In a meta-analysis, Paolucci, Genuis, and Violato (2001) found the average unweighted and weighted ds for the relationship between sexual abuse (any unwanted sexual contact) and suicidality (suicidal ideation, plan or attempt) were .64 and .44, respectively. In a recent meta-analysis, Devries et al (2014) found childhood sexual abuse to be associated with suicide attempts even when a range of different confounders (including other types of abuse and parental pathology) were controlled. Specifically, the overall pooled estimate for the longitudinal studies was OR D 2.43, and the pooled OR from co-twin analysis was 2.65.…”
Section: Ace and Suicidementioning
confidence: 99%
“…Following a systematic review of 52 studies, Miller et al (2013) found that CSA was associated with adolescent suicidal ideation and suicide attempts in community as well as clinical samples, relying on both cross-sectional and longitudinal designs, even when controlling for demographics and possible confounder variables (youth mental health, family adversities). Devries et al (2014) in a meta-analysis of longitudinal and twin studies concluded that CSA was associated with increased risk of suicide attempts after controlling for genetic risk factors and family adversity. Given the well-known deleterious impact of CSA, it is essential to identify factors underlying the emergence of symptoms and accounting for the diversity of outcomes in survivors.…”
Section: Introductionmentioning
confidence: 99%